2016
DOI: 10.1016/j.anucene.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

XGPT: Extending Monte Carlo Generalized Perturbation Theory capabilities to continuous-energy sensitivity functions

Abstract: a b s t r a c tThe XGPT method extends the Generalized Perturbation Theory capabilities of Monte Carlo codes to continuous-energy sensitivity functions. In this work, this method is proposed as a new approach to nuclear data uncertainty propagation. XGPT overcomes some of the limitations of legacy perturbationbased approaches. In particular, it allows the nuclear data uncertainty propagation to be performed adopting continuous energy covariance matrices, instead of discretized (multi-group) data. The XGPT capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…They have already been used and characterized in previous work, see for instance references [2,3,26]. All possible nuclear data are varied, such as cross sections, angular distributions, emitted spectra and multiplicities.…”
Section: Correlation From Integral Benchmarksmentioning
confidence: 99%
See 1 more Smart Citation
“…They have already been used and characterized in previous work, see for instance references [2,3,26]. All possible nuclear data are varied, such as cross sections, angular distributions, emitted spectra and multiplicities.…”
Section: Correlation From Integral Benchmarksmentioning
confidence: 99%
“…Many simulation tools are capable of using such matrices to propagate nuclear data uncertainties on final quantities, with either perturbation theories [1][2][3][4][5][6], or Monte Carlo sampling [3,[7][8][9][10][11][12][13]. These results can for instance be used for the review procedure of new facilities, or during the safety assessment of new reactor core designs [14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, POD was introduced to study the coherent structures in experimental turbulent flows. In the nuclear field (as in other fields of engineering), it has been shown that POD basis functions carry out physical information on distribution of scalar and energy group fluxes, fluid velocity distributions in thermal-hydraulics and cross section uncertainties [21][22][23][24]. For this reason, we expect that POD modes for burnup matrices and fluxes provide the main physical information on fuel burnup.…”
Section: Motivation Of the Methodologymentioning
confidence: 97%
“…In the nuclear field, POD has been successfully applied to neutronics [21][22][23], thermal-hydraulics [24], sensitivity and uncertainty quantification [25,26]. Notwithstanding, there is a lack of literature in the employment in burnup calculations, nevertheless it would be necessary to solve the issue of computational burden previously discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Carlo method have been developed (Choi and Shim, 2016b;Qiu, et al, 2016a;Perfetti and Rearden, 2016;Aufiero et al, 2016), the present paper focuses on the sensitivity analysis of keff-eigenvalue. This paper scrutinizes the source perturbation effect on a sensitivity coefficient due to the change of nuclear data through the multi-group Monte Carlo calculations.…”
Section: While the Sensitivity Analysis Methods For Generalized Respomentioning
confidence: 99%